Exploring Hui Muslims’ utilization of Islamic Press for the revival of Islam during the Republic of China (1912-1949) - Mai, Jianjun; Shehu, Fatmir Mehdi (IIUM Press, 2021)
This paper seeks to explore the utilization of Islamic Press by Hui Muslims for the revival of Islam during the Republic of China (1912-1949). The goal of this study is to show how the Hui Muslim Da’wah practitioners including intellectuals and Islamic scholars used Islamic Press, i.e., Islamic newspapers and journals, as the main Islamic Da‘wahinstrument to revive Islam and its teachings among the Hui Muslims as well as convey Islamic Message to non-Muslims. The research brings important insights into Islamic Da‘wahefforts made by the Hui Muslims in the history of Islamic Revival Movement in China. The focus of discussion is on: origin of Hui Muslims; background of the Islamic Revival Movement; and Islamic Press. The historical, descriptive, and analytical methods are used in the entire research. This work finds out that the Hui Muslims during the Republic of China have responded proactively to the social and political changes in the Chinese society to advance the cause of Islamic Da‘wah. By adapting to the environment and using the advanced available technology, it indicates their use of Hikmah(wisdom) in conducting the work of Islamic Da‘wah.